Response Analysis of Three-Detector Neutron Porosity Logging Based on D-D Source - ZHOU Yue; WANG Meng; LIU Haibo; SHANG Xiusheng; LIU Zhijie (Cejing jishu)
With the continuous deepening of oil and gas exploration, low porosity reservoirs are receiving more and more attention. D-D neutron logging with higher porosity sensitivity has a good application prospect, a three probe neutron porosity logging based on D-D source is proposed and analyzed for the purpose of exploring its possibility of combining porosity measurement sensitivity and chemical source measurement compatibility. This study aims to explore the response characteristics of D-D source neutron porosity logging. By using Monte Carlo method, a three-detector neutron porosity logging tool's detector spacing is designed and it is proposed to measure thermal neutron near-to-far ratio and middle-to-far ratio to characterize the porosity of the formation, meanwhile, formation detection ability and measurement response of D-D source neutron porosity logging are analyzed. The results show that three-detector neutron porosity logging tool based on D-D source has a slightly shallower detection depth and higher vertical resolution. Thermal neutron near-to-far ratio's response shows good sensitivity to formation porosity and good response in low porosity formation. Thermal neutron middle-to-far ratio's response cannot be compatible with traditional radioactive measurements and its mudstone effect is strong, but it is highly similar to radioactive measurements in conventional lithology and shaly reservoirs. This study provides a reference value for D-D source neutron porosity logging tool application.